THE RELATIONSHIP BETWEEN SELF-COMPASSION AND LEARNING ANXIETY OF STUDENTS OF STATE SENIOR HIGH SCHOOL 11 MUARO JAMBI - Setyaningsih, Mukti Lestari; Nelyahardi, Nelyahardi; Yusra, Affan (Jurnal Kopendik, 2025)
This study aims to determine the levels of self-compassion and learning anxiety, as well as the relationship between self-compassion and learning anxiety among students of SMA Negeri 11 Muaro Jambi. The research used a quantitative correlational method with a Simple Random Sampling technique involving 72 students from grades X, XI, and XII in the 2024/2025 academic year. Data were collected using a Likert scale questionnaire. The results showed that students’ self-compassion was in the high category (67%), while learning anxiety was in the moderate category (48%). The correlation test indicated a significant negative relationship between self-compassion and learning anxiety (r = -0.563, p < 0.05). This means that the higher the students’ self-compassion, the lower their learning anxiety. The findings imply that developing self-compassion through Guidance and Counseling services can be an effective strategy to reduce learning anxiety and enhance students’ psychological well-being.